Given the function f (x) = 9x + 7, find its inverse.

let y = 9x+7

the inverse is x = 9y+7

solving this for y
9y= x-7
y = (x-7)/9 <------ that's the inverse
or
f^-1 (x) = (x-7)/9

To find the inverse of a function, we need to switch the x and y variables and solve for y.

Step 1: Start with the given function: f(x) = 9x + 7

Step 2: Replace f(x) with y: y = 9x + 7

Step 3: Swap x and y: x = 9y + 7

Step 4: Solve for y: Subtract 7 from both sides of the equation: x - 7 = 9y

Step 5: Divide both sides of the equation by 9 to isolate y: (x - 7)/9 = y

Step 6: Replace y with f^(-1)(x), the inverse function: f^(-1)(x) = (x - 7)/9

Therefore, the inverse function of f(x) = 9x + 7 is f^(-1)(x) = (x - 7)/9.

To find the inverse of a function, we need to swap the x and y variables and then solve for y.

Step 1: Replace f(x) with y:
f(x) = 9x + 7 ---> y = 9x + 7

Step 2: Swap x and y variables:
x = 9y + 7

Step 3: Solve for y:
x - 7 = 9y

Step 4: Divide both sides by 9:
(x - 7)/9 = y

Therefore, the inverse function of f(x) = 9x + 7 is f^(-1)(x) = (x - 7)/9.